Presence of Eisenia fetida enhanced phytoremediation of anthracene by Lolium perenne - Ghavidel, Akbar (2018)
The efficiency of co-application of Eisenia fetida and ryegrass was evaluated in a process called earthworm-assisted phytoremediation. Anthracene was used as a model compound for polycyclic aromatic hydrocarbons (PAHs). The experiments were conducted on a loamy soil in greenhouse conditions. At the end of the experiment, the soil samples were analyzed for residual anthracene by HPLC. Results showed that, phytoremediation using ryegrass could remove 81% of anthracene; however, the rate of removal was 92% when E. fetida was applied simultaneously. E. fetida alone could also remove the initial concentration of anthracene by 40%. Although ryegrass itself could remove anthracene significantly, the employment of earthworm, together with plant was more efficient than each of them individually. The application of E. fetida could also enhance the growth parameters of ryegrass significantly. In comparison to the control, the presence of E. fetida increased plant dry weight (7.8%), root length (47%), shoots length (32%), and root volume (12%). The number of live earthworms was also increased in the planted pots, indicating the helpfulness of the plant for survival of the earthworm in the PAH-contaminated soil. Although plant and earthworm use completely different mechanisms for anthracene degradation, they improve efficiency and survival of the three-component-system.